Role of inhibitors and biodegradable material in mitigation of nitrogen losses from fertilized lands - Junejo, Nasima; Yusop, Mohd Khanif; Musa, Mohamed Hanafi; Wan Yunus, Wan Md. Zin; Dharejo, Khalil Ahmed (Academic Journals, 2011)
Loss of N, occurring mainly through NH3 volatilization, biological denitrification, and NO3 - leaching, has both economic and environmental implications. Therefore, the economic benefits of reduced environmental pollution and future damage to our environment as a result of the use of urease inhibitors are of higher significance to the production of gains over the long-term. The literature review discussed the role, effectiveness and mechanism of urease inhibitors as well as coating of urea to reduce ammonia volatilization loss from urea fertilizer. Coating with urease inhibitors can improve the bioavailability of N, resulting in increased dry matter yield and N uptake. Such increases result from delayed urea hydrolysis by urease inhibitors and coating materials. The value of inhibitors in mitigating N loss would depend on their rate of biodegradation and persistence in soils. Previous studies has proven that micronutrients could be competent urease inhibitors, but the information about their effects on soil, nutrient uptake of plants and dry matter yield is poorly documented. Some nutrients such as Cu and Zn as urease inhibitors and natural biodegradable material such as agar, gelatin and palm stearin were found effective in reduction of nitrogen losses from nitrogen fertilizer especially from urea fertilizer. The article deals with the importance of use of above mentioned materials and micronutrient.